El fantasma de la libertad [videorecording (DVD)] - Brialy, Jean-Claude; Celi, Adolfo, 1922-1986; Piccoli, Michel, 1925-2020 (StudioCanal, 2018)
This surrealist film consists of a series of only vaguely related episodes, most famously the dinner party scene in which people sit on lavatories round a dinner table, occasionally retiring to a small room to eat.